Influence Mechanism of Ionic Interface Reaction on Soil Porosity - Song Xiaoshuai; He Jiahong; Ding Wuquan; Liu Xinmin (Shuitu baochi tongbao)
[Objective] The changes in surface charge properties of soil particles and the net force between particles were analyzed, in order to elucidate the influence mechanism of particle interaction on pore conditions. [Methods] Soil pore conditions under different valence ion conditions were measured and the differences in soil pore characteristics formed by them were analyzed using industrial CT scanning techniques. [Results] ① The number of soil pores under the Mg2+ system was much larger (1.43 times) than the number of soil pores under the Na+ system. The number of soil pores (>1 mm) accounted for 1.43% and 1.06% of the total number of pores for the two respective systems. ② The pore volume of the soil pores (>1 mm) accounted for 50.4% and 40.2% of the total pore volume of the two respective systems. Additionally, the volume of the soil pores (>1 mm) for the Mg2+ system was 1.42 times higher than for the Na+ system. Soil porosity in the soils of the Na+ and Mg2+ systems was 2.06% and 2.35%, respectively. ③ As the concentrations of Na+ and Mg2+ increased, the surface potential of purple soil decreased from -391.7 mV to -96.7 mV and from -167.3 mV to -67.0 mV, respectively. At the same concentration, the surface potential (absolute value) of purple soil showed that Na+ exhibited greater performance than Mg2+. ④ The net force between soil particles decreased with increasing Na+ and Mg2+ concentrations. At the same concentration, the electrostatic repulsion between purple soil particles in the Mg2+ system was smaller than in the Na+ system. The critical concentration values of the net gravitational force exhibited between purple soil colloidal particles in the Na+ and Mg2+ systems were 0.1 mol/L and 0.005 mol/L, respectively. [Conclusion] Na+ and Mg2+ changed the pore condition of the soil by changing the surface charge properties of purple soil particles, which in turn caused changes in the interaction forces between soil particles, ultimately affecting the pore condition of the soil.